2014
DOI: 10.4085/1062-6050-49.1.01
|View full text |Cite
|
Sign up to set email alerts
|

The Persistent Influence of Concussive Injuries on Cognitive Control and Neuroelectric Function

Abstract: Context: Increasing attention is being paid to the deleterious effects of sport-related concussion on cognitive and brain health.Objective: To evaluate the influence of concussion incurred during early life on the cognitive control and neuroelectric function of young adults.Design: Cross-sectional study. Setting: Research laboratory.Patients or Other Participants: Forty young adults were separated into groups according to concussive history (0 or 1þ). Participants incurred all injuries during sport and recreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 79 publications
3
39
0
Order By: Relevance
“…Studies have indicated that there may be neurocognitive deficits from concussion that persist past the point of return to play [31, 32] that current clinical neurocognitive assessments may not be able to detect under current standard testing protocols [33, 34]. Similarly, there is a growing body of evidence that persistent neuromuscular performance impairments are present in concussed athletes during relatively simple gait tasks; furthermore, these impairments are more prominent when a concomitant dual-attention cognitive task is employed [39].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that there may be neurocognitive deficits from concussion that persist past the point of return to play [31, 32] that current clinical neurocognitive assessments may not be able to detect under current standard testing protocols [33, 34]. Similarly, there is a growing body of evidence that persistent neuromuscular performance impairments are present in concussed athletes during relatively simple gait tasks; furthermore, these impairments are more prominent when a concomitant dual-attention cognitive task is employed [39].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings related to persistent changes in the P3a component have been reported in previously concussed participants 22 to 60 months [60], 3.4 years [8], and 26 years [15] post-injury. To a lesser extent, suppressed Ne has been shown at 2.9 years [47], suppressed P1 amplitude at 6.7 years [45], and an altered N2 component at 7.1 years post-injury [46]. While these findings were generated in response to the target stimuli during a visual task, compared to the auditory task implemented here, it is possible that ongoing deficits may need to be accounted for by clinicians when interpreting post-concussion results.…”
Section: Discussionmentioning
confidence: 99%
“…Flanker tasks require individuals to ignore task-irrelevant information in order to correctly respond to a centrally presented target stimulus amid either congruent or incongruent flanking stimuli. While conceptually simplistic, this task has demonstrated high sensitivity for detecting deficits from years (Moore, Hillman, & Broglio, 2014;) to decades (de Beaumont, Brisson, Lassonde, & Jolicoeur, 2007) following injury in adults. This sensitivity is due to the rich variety of cognitive processes/effects, which can be evaluated during flanker performance.…”
Section: Introductionmentioning
confidence: 99%